2015
DOI: 10.1080/19443994.2015.1043492
|View full text |Cite
|
Sign up to set email alerts
|

Removal of mercury (II) from the aquatic environment by phytoremediation

Abstract: A B S T R A C TPhytoremediation may be an alternative to traditional methods of removing heavy metals from the aquatic environment. In order to remove mercury at a concentration of 0.3 mg/L from Hoagland medium, two species of pleustophytes were used, namely Salvinia natans and Lemna minor. Some homogeneous cultures and another one mixed in a weight ratio of 2:1 were used. The physiological condition of the plants was controlled after 7, 14 and 21 d by evaluating biomass growth, analysing the changes in the am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…The presence of bacteria enhanced phytoaccumulation relative to the uninoculated plants, by up to 650 and 320 mg Pb kg −1 and up to 7.5 and 2.4 mg Hg kg −1 in roots and shoots respectively [144]. Growth and Hg 2+ uptake capacities were improved in Salvinia natans and Lemna minor grown in aqueous solution containing 0.3 mg Hg(NO 3 ) 2 L −1 , by the presence of three strains of epiphytic bacteria [145]. Hg-resistant Enterobacter ludwigii and Klebsiella pneumoniae, isolated from of 37…”
Section: Non-rhizobial Associationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of bacteria enhanced phytoaccumulation relative to the uninoculated plants, by up to 650 and 320 mg Pb kg −1 and up to 7.5 and 2.4 mg Hg kg −1 in roots and shoots respectively [144]. Growth and Hg 2+ uptake capacities were improved in Salvinia natans and Lemna minor grown in aqueous solution containing 0.3 mg Hg(NO 3 ) 2 L −1 , by the presence of three strains of epiphytic bacteria [145]. Hg-resistant Enterobacter ludwigii and Klebsiella pneumoniae, isolated from of 37…”
Section: Non-rhizobial Associationsmentioning
confidence: 99%
“…The presence of bacteria enhanced phytoaccumulation relative to the uninoculated plants, by up to 650 and 320 mg Pb kg −1 and up to 7.5 and 2.4 mg Hg kg −1 in roots and shoots respectively [ 144 ]. Growth and Hg 2+ uptake capacities were improved in Salvinia natans and Lemna minor grown in aqueous solution containing 0.3 mg Hg(NO 3 ) 2 L −1 , by the presence of three strains of epiphytic bacteria [ 145 ]. Hg-resistant Enterobacter ludwigii and Klebsiella pneumoniae , isolated from Alternanthera sessilis and Cyperus esculentus , growing on a Hg-contaminated site individually stimulated growth, lowered proline, malondialdehyde content, and electron leakage in commercial Triticum aestivum seedlings under 75 μM HgCl 2 in hydroponics [ 146 ].…”
Section: Microorganisms-assisted Hg Phytoremediationmentioning
confidence: 99%
“…Hamzah et al (2015) found that the presence of bacteria increased phytoaccumulation of Hg in shoots (by up to 7.5 mg kg −1 ) in comparison to uninoculated plants. Sitarska et al (2016) reported on enhanced growth and Hg 2+ absorption capabilities of Salvinia natans and Lemna minor cultivated in a water solution comprising 0.3 mg L −1 Hg(NO 3 ) by three strains of epiphytic bacteria. Franchi et al (2017) examined a group of five Hg/As‐resistant bacteria in conjunction with thiosulphate, a fertiliser that acts as a metal mobilising agent.…”
Section: Phytoremediationmentioning
confidence: 99%
“…Brevundimonas diminuta SF-S1-5 and Alcaligenes faecalis SF-S1-60, two heavy metal-resistant rhizobacteria, significantly assisted Scirpus mucronatus growth in sand soil contamined by a mixture of Pb (100 mg kg À1 ) and Hg (1 mg kg À1 ) Hamzah et al (2015). found that the presence of bacteria increased phytoaccumulation of Hg in shoots (by up to 7.5 mg kg À1 ) in comparison to uninoculated plants Sitarska et al (2016). reported on enhanced growth and Hg 2+ absorption capabilities of Salvinia natans and Lemna minor cultivated in a water solution comprising 0.3 mg L À1 Hg(NO 3 ) by three strains of epiphytic bacteria.…”
mentioning
confidence: 95%
“…This technology is environment friendly and potentially cost-effective. The potential of aquatic macrophytes for heavy metal removal has been investigated and reviewed thoroughly (Ahmad et al 2014(Ahmad et al , 2015Devlin 1967;Ellis et al 1994;Kara et al 2003;Marques et al 2009;Rahman et al 2008;Rai 2005;Sharma and Gaur 1995;Sitarska et al 2015;Vymazal 1995). Ahmad et al (2014Ahmad et al ( , 2015 recently reported the heavy metal removal capability of Ceratophyllum demersum, Phragmites australis and Potamogeton natans in Hokersar wetland -an important Ramsar site in the Kashmir Himalaya, India.…”
Section: Introductionmentioning
confidence: 99%